New species and records of grammitid ferns (Polypodiaceae) for Vietnam - Parris, Barbara; Chen, Cheng Wei; Hsu, Tian Chuan; Lu, Thi Ngan; Nguyen, Quoc Dat; Luu, Hong Truong (Phytotaxa, 2015)
Three new species (Calymmodon concinnus, Oreogrammitis parvula, Xiphopterella parva), and seven new records (Dasygrammitis brevivenosa, Oreogrammitis sinohirtella, Radiogrammitis beddomeana, R. jagoriana, Scleroglossum pyxidatum, S. sulcatum and Themelium halconense) of grammitid ferns (Polypodiaceae) are reported for the flora of Vietnam, mostly from newly collected specimens. We provide detailed morphological descriptions, illustrations, ecology and distribution, and taxonomic notes for each new species. Furthermore, type information, distribution, voucher specimens and taxonomic notes are provided for each newly recorded species. A checklist including synonymy and a key to Vietnamese grammitid ferns are also given.